2013
DOI: 10.1590/s0103-90162013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Mulch materials in processing tomato: a multivariate approach

Abstract: Mulch materials of different origins have been introduced into the agricultural sector in recent years alternatively to the standard polyethylene due to its environmental impact. This study aimed to evaluate the multivariate response of mulch materials over three consecutive years in a processing tomato (Solanum lycopersicon L.) crop in Central Spain. Two biodegradable plastic mulches (BD1, BD2), one oxo-biodegradable material (OB), two types of paper (PP1, PP2), and one barley straw cover (BS) were compared u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
1
11
1
1
Order By: Relevance
“…The infl uence of the L color variable on total variability was observed in a previous study by Moreno et al (2013), in line with Ordóñez-Santos et al (2008). The current study also shows the great infl uence of both juice color and lycopene and the expected relationship between them (Gómez et al, 2001), the importance of the fi rmness and the relationships among the different quality variables and mulches (Table 3, Figure 1).…”
Section: Multivariate Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…The infl uence of the L color variable on total variability was observed in a previous study by Moreno et al (2013), in line with Ordóñez-Santos et al (2008). The current study also shows the great infl uence of both juice color and lycopene and the expected relationship between them (Gómez et al, 2001), the importance of the fi rmness and the relationships among the different quality variables and mulches (Table 3, Figure 1).…”
Section: Multivariate Analysissupporting
confidence: 89%
“…Both papers, PP1 and PP2, were also grouped together, contrary to those obtained by Moreno et al (2013), who found that PP2 was more closely associated with the group of the plastic mulches including PE, OB and BD2, whereas PP1 was more similar to MW. This fi nding confi rms the discriminant effect of the variables related to weed control and, consequently, to yield, on both papers.…”
Section: Multivariate Analysiscontrasting
confidence: 77%
See 2 more Smart Citations
“…A number of studies have recently analysed the agronomic and environmental performance of paper mulch (Martin-Closas et al, 2003;Moreno et al, 2013;Haapala et al, 2014), polyethylene with additives for degradation or biodegradable films (Filippi et al, 2011;Saraiva et al, 2012;Benincasa et al, 2014). By conducting field experiments, these studies showed that these potential substitutes of conventional films offer the advantage of degrading into non-toxic components.…”
Section: Introductionmentioning
confidence: 99%